Basal and postprandial gastrin levels in the early neonatal period - Aydın, Ahmet; Haktan, Makbule; Çakır, Erol (The Turkish Journal of Pediatrics, 1986)
We investigated the basal and postprandial serum levels of gastrin in 60 full-term healthy infants in the early neonatal period. Basal values in cord blood and in the peripheral veins of these babies before the first feeding (3-7 hours), and on the second and seventh days were similar to each other and higher than the basal values of adults. Despite the sufficient parietal cell mass and high serum gastrin levels, the hyposecretion of gastric acid in newborns suggests that the parietal cells of newborn infants lack gastrin receptors. Pre- and postprandial serum gastrin values on the first and seventh day did not demonstrate a significant difference. These results show that serum gastrin levels are maximal under basal conditions in the early neonatal period and also suggest that antral gastrin concentrations are extremely low as a result of maximal G-cell hypersecretions.
Keywords: gastric acid secretion; gastrin receptor; newborn; postprandial serum gastrin level